Tradisi Bezikir sebagai Media Komunikasi Budaya Masyarakat Desa Pulau Panggung Kabupaten Kaur - Feby Lajua Jaya; Sri Dwi Fajarini (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to analyze the Bezikir tradition as a medium of cultural communication in the community of Pulau Panggung Village, Luas Subdistrict, Kaur Regency. The study employs a descriptive qualitative approach, involving five informants consisting of the traditional leader, members of the kendaur (Bezikir practitioners), community leaders, and community members who understand the practice of the Bezikir tradition. Data were collected through participant observation, in-depth interviews, and documentation. Data analysis was conducted using the Miles, Huberman, and Saldaña model, which includes data reduction, data presentation, and drawing conclusions, while data validity was tested through source triangulation and member checking. The research findings indicate that the Bezikir tradition functions not only as a series of wedding customs but also as a medium of cultural communication that plays a role in transmitting religious values, social solidarity, respect for ancestors, and the cultural identity of the Kaur community. The communication process occurs through interactions between traditional practitioners, the bride and groom, families, and the community members present at the ritual. Cultural symbols such as the gendang, the recitation of the Maulid Saiful Anam, ritual movements, and collective community participation are interpreted as representations of gratitude, togetherness, and hope for a harmonious married life. The research findings also indicate that the Bezikir tradition serves as a means of transmitting cultural values across generations while strengthening social cohesion within the community.This study contributes to the development of cultural communication studies by demonstrating that local traditions can be understood as spaces for the exchange of symbols and the construction of cultural meaning. Practically, the research findings have implications for efforts to preserve the Bezikir tradition through strengthening the role of customary institutions, local cultural education, and the involvement of the younger generation in ensuring the sustainability of the region’s cultural heritage. Keywords: cultural communication, Bezikir tradition, ritual communication, cultural symbols, local culture.